The Proprieties of Stigma and the Situation of Human Life in Danger of Stigma - Świgost, Magdalena (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
It is stated that the properties of stigma have the key role in perceiving social relations and own life situation by the person who is in danger of the process of social stigma (Davidio, Major and Crocer, 2008, p. 27–28). It is cognitively interesting how agreeing to the process of social stigma is shown in terms of difficulty that is being activated by specific feature, pressing, in exceptional sense, on seeing and controling the stigma. This article contains the theoretical analysis of the process of social stigma in relation to its chosen features. There has been done an attempt to present mutual assorted interaction with the influence of blocking predicators or those restoring the process of social self-indicating and indicating